Application of Intelligent Optimization Technology for Territorial Spatial Planning Based on Edge Network. (1st October 2021) - Mei, Yu
Abstract : As a new type of planning after the national sectoral adjustment, there is an overall lack of methodological research on the preparation of territorial spatial planning, and scholars mainly focus on the endowment of natural resources themselves, using traditional statistics, spatial and survey data and statistical analysis, spatial analysis and inductive deduction to statically evaluate the spatial carrying capacity and suitability of the national and provincial level and to make a static evaluation of ecological red line, basic farmland protection line, and The existing studies, however, have not taken into account the human and the environment. However, the existing studies seldom consider the dynamic impact of human activities on the spatial utilization of national land and lack scientific arrangement of ecological space, agricultural space, and urban space under the new development trend. This paper introduces big data that can directly reflect the spatial and temporal changes of human activities and discusses the direction and specific methodological framework of edge network-based optimization technology from four aspects: spatial suitability evaluation, ecological spatial planning, agricultural spatial planning, and urban spatial planning, emphasizing that "natural space" + "socio-economic activities" are mutually beneficial. The scientific path of territorial spatial planning under the interaction of "natural space" + "socio-economic activities" is emphasized.